PENGARUH DUKUNGAN KELUARGA DAN DUKUNGAN TENAGA KESEHATAN TERHADAP PEMBERIAN ASI EKSKLUSIF - ., Sohimah (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Exclusive Breastfeeding (ASI) is a living liquid that can adjust the content of substance that can meet the nutritional needs of infants (Maryunani 2012). Based Riset Kesehatan Dasar (Riskesdas) of 2013 infants exclusively breastfeeding for six months is only 40.6%, far from the national target of 80%. The problems in the practice of exclusive breastfeeding is the social and cultural factors of economic (family support, education, income and employment status mothers), factors maternal age (readiness mothers in breastfeeding), factor parity mother, a factor of support from family, factor a lack of staff health and support community health workers making less light or encouragement about the benefits of exclusive breastfeeding. The purpose research this is to know the effect of family support and support of health workers on exclusive breastfeeding in Puskesmas Cilacap Tengah1 Kabupaten Cilacap. Methods This research is an explanatory research using cross sectional method. Subject Research This is the infant more 6 months and less of 12 months. Sample selection techniques that will be used in this research is cluster random sampling. Analysis of the data in this study conducted by Chi Square. Results of the research that no influencing to exclusive breastfeeding of health workers (p value 0,513 > 0,05) and factor Support family significant  influencing to exclusivebreastfeeding (p value 0,000 <  0,05) No influencing to exclusive breastfeeding of health workers and Support family factor significant  influencing to exclusive breastfeeding. Keywords: exclusive breastfeeding, support, family, labor health